O efeito imediato da Estimula????o El??trica Transcraniana por Corrente Cont??nua (ETCC) associada ao uso da FES na atividade do m??sculo tibial anterior e equil??brio, de indiv??duos com hemiparesia decorrente de AVE ??? estudo randomizado, controlado, duplo cego - Fruhauf, Aline Marina Alves (2016)
Increased cortical activity induced by brain stimulation, associated or not with other rehabilitation techniques, may potentiate the therapeutic effects in patients with neurological deficits. To assess the immediate effects of two related techniques, transcranial direct-current stimulation (tDCS) and functional electrical stimulation (FES), the electrical activity of the tibialis anterior (TA) and static balance of individuals with post stroke hemiparesis. Methods: clinical trial, controlled, randomized, double-blind, 30 individuals hemiparesis due to stroke. Rating: median frequency and RMS TA by electromyography (EMG) and evaluation of static balance (area, speed and frequency of oscillation in open eyes (OE) and closed (CE)) by stabilometry. Interventions: 4 protocols with 48h interval: 1 (tDCS anodic + FES sham), 2 (tDCS sham + FES active), 3 (tDCS anodic + FES active) and 4 (tDCS sham + FES sham). The anode was applied on etcc C3 and / or C4 and cathode on the contralateral supraorbital region and FES on hemiparetic TA for 20 minutes. Results: There was no statistically significant difference (p> 0.05) of the median frequency and RMS for the acquisition of isotonic and maximal voluntary isometric contraction (MVIC) of TA and static balance both OE and CE condition of the protocols by the Friedman test . Conclusion: There was no difference in the electrical activity of the TA muscle and static balance after application of the associated technical or isolated. The application time may not be enough to verify a motor learning, moreover, it is suggested that the tDCS may have a cortical hyperexcitability generated response any competitor inhibiting action; and a second hypothesis is that the stimulation of both the FES or active contraction has generated supposed peripheral fatigue, even with preconization contractions to avoid that this factor. It is believed that the two suggestive lead to additive effects (a technique inhibiting possibly other).